SEROPREVALENCE AND PROFILE ANTI-VIRUS OF NEWCASTLE DISEASE POST-VACCINATION ON LOCAL CHICKEN IN BOBONARO DISTRICT TIMOR-LESTE - Joao, Alberto Agustinho Pereira Da Costa; Astawa, I Nyoman Mantik; Adi, Anak Agun Ayu Mirah (Buletin Veteriner Udayana, 2022)
The objective of this study was to determine anti-Newcastle disease virus (NDV) antibody titres in sera samples of pre-vaccinated and post-vaccinated local chickens in the villages of Lahomean, Odomau Raifun and Ritabou, Bobonaro District Timor-Leste. Eighty sera samples of pre-vaccinated and 79 samples of post-vaccinated chickens were collected from village chicken farms bred extensively in all four villages. The sampling techniques adopted were simple random and purposive sampling methods to select subjects based on predetermined criteria. Antibody titers against NDV in serum samples were examined by using hemagglutination test (HA) and hemagglutination inhibition test (HI). The data obtained in this studi were presented descriptively. The results showed that of 80 sera samples collected from pre-vaccinated chickens, 53 (66.25%) sera samples were seronegative with the antibody titers of < 2 3 (2 1 – 2 3 ) HI units and 27 (33,75%) sera samples were seropositive with antibody titers of 2 4 – 2 10 HI units. As for 79 sera samples collected from post-vaccinated chickens, 46 (57%) samples were seronegaitive with the antibody titers of 2 1 – 2 3 HI and 33 (43%) sera samples were seropositive with antibody titer of 2 4 – 2 11 HI units. The results showed that presence of anti-NDV antibody in prevaccinated chickens was very likely due to the natural infection and vaccination increased the titers and the number of seropositive chickens.